Word meanings in the New Testament - Earle, Ralph (Grand Rapids, MI Baker, 1986)
Includes indexes.
Originally published in six volumes : v. 1: Matthew - Luke, 1980; v. 2 : John - Acts, 1982; v. 3 : Romans, 1974; v. 4 : I Corinthians - Ephesians, 1979; v. 5 : Philippians - Philemon, 1977; v. 6 : Hebrews - Revelation, 1984.
Keywords: Bible. N.T. -- dictionaries